1952
DOI: 10.1017/s0080456800009297
|View full text |Cite
|
Sign up to set email alerts
|

VIII.—Structure and Biology of the Larva and Spat ofVenerupis pullastra(Montagu)

Abstract: Synopsis:This is a study of the structure and biology of the lamellibranchVenerupis pullastra(Montagu) from the early larva to the spat stage. The larva is identified, and the functional significance of the changes that occur during metamorphosis from the larva to the spat is considered. Organ development in the spat up to a length of one millimetre is described. The free swimming larva is studied from the point of view of seasonal abundance, length of pelagic period, vertical distribution and diurnal migratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
0

Year Published

1973
1973
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 31 publications
5
23
0
Order By: Relevance
“…Galtsoff (1964) stated that the eyespots broke up into irregular clumps of pigment, The dorsal movement and elongation of the eyespot into the eyestreak has not been reported previously. Our observation that the labial palps are pigmented in those oysters in which the velum was pigmented, corroborates the conclusions of Cole (1938), Quayle (1951) and Galtsoff (1964) that the labial palps develop from the apical portion of the velum. The speed at which metamorphosis occurs varies considerably between individuals.…”
Section: Discussionsupporting
confidence: 91%
“…Galtsoff (1964) stated that the eyespots broke up into irregular clumps of pigment, The dorsal movement and elongation of the eyespot into the eyestreak has not been reported previously. Our observation that the labial palps are pigmented in those oysters in which the velum was pigmented, corroborates the conclusions of Cole (1938), Quayle (1951) and Galtsoff (1964) that the labial palps develop from the apical portion of the velum. The speed at which metamorphosis occurs varies considerably between individuals.…”
Section: Discussionsupporting
confidence: 91%
“…These authors' viewpoint is supported by similar comments with respect to the larvae of barnacles (Bousfield 1955), fish (Fortier & Leggett 1983), brachyuran crabs (see contributions in Kennedy 1982;Sulkin 1984) and even dinoflagellates (Tyler & Seliger 1978. Quayle (1952) examined vertical distribution of Venerupis pullastra (Montagu) larvae in Scottish coastal waters and concluded that they perform active die1 migrations, being near the surface at night and at certain tidal phases, and nearer the bottom in the daytime. By contrast Korringa (1952) suggests that larvae are predominantly passive drifters.…”
Section: Yes Yesmentioning
confidence: 82%
“…In a 10 m mesocosm, sea scallop larvae moved from a mean depth of 6.9 m during the day to 3.7 m at night (Silva & O'Dor 1988), and Pecten maximus larvae also occur shallower at night in experimental water columns (Kaartvedt et al 1987). Field studies of other species of bivalve larvae (Quayle 1952(Quayle , 1959 and total bivalve larvae (Harding et al 1986, Scrope-Howe & Jones 1986) have also found this pattern.…”
Section: Discussionmentioning
confidence: 93%
“…Active migration of late stage oyster larvae in relation to tidal circulation within some estuaries has been reported (Nelson & Perkins 1931, Carriker 1951, Kunkle 1958, although there are other interpretations of these data which do not involve larval behavior (Korringa 1952, de Wolf 1973, Andrews 1983. Diel vertical migration of some coastal bivalve larvae (Quayle 1952, 1959, Verwey 1966, Harding et al 1986, and offshore bivalve larvae (Scrope-Howe & Jones 1986) is suggested by the occurrence of the larvae in shallower depths at night.…”
Section: Introductionmentioning
confidence: 99%